Karialılar: denizcilerden kent kuruculara = The Carians : from seafarers to city builders - Henry, Olivier; Belgin-Henry, Ayşe (Yapı Kredi yayınları, 2020)
Presents a brief overview of archaeological and historical research on Caria from the very first signs of occupation in the Prehistoric times to the Late Ottoman period. The region occupied by ancient Caria can roughly be described as the southwestern portion of the Anatolian peninsula South of the Menderes Valley and west of the Dalaman River. The Carians are mentioned several times in the 2nd millennium BCE for having supported the fight of Anatolian nations against the Hittite invaders and later to have fought beside the Hittite kings against the Egyptian forces. They were also counted amongst the legendary Sea People, traveling the Mediterranean, spreading destruction on their path and bringing down some of the most powerful empires of the Late Bronze Age. Later, Homer mentions them in the list of allies who came and supported Troy against the Greeks, emphasizing the wealth of the Carians, who "came to fight decked like a girl with gold"
Includes bibliographical references and index
Keywords: Geschichte; Archäologische Stätte; Karien